1989
DOI: 10.1002/etc.5620080109
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of aquifer microbial communities to the biodegradation of xenobiotic compounds: Influence of substrate concentration and preexposure

Abstract: Studies were conducted to examine the adaptation response of aquifer microbial communities to xenobiotic compounds and the influence of chemical preexposure in the laboratory and in situ on adaptation. Adaptation and biodegradation were assessed as mineralization and cellular incorporation of 14C‐radiolabeled substrates. For some compounds, such as ethylene dibromide, aniline and m‐nitrophenol, biodegradation and adaptation rates were not influenced by chemical concentration over the range tested. Biodegradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…Metabolic adaptation by subsurface microorganisms to environmental pollutants at field sites can be documented using two principal types of criteria: the response may be qualitative, i.e., metabolism may be present in contaminated samples and absent in adjacent uncontaminated samples [6,20,32,35], or the response may be quantitative, i.e., prior exposure of microorganisms to a pollutant may shorten the lag period prior to the onset of metabolic activity [1,2], increase the rate or extent of metabolism, or enhance the proportion of the pollutant that is respired [2]. The presence of a control site that is uncontaminated, adjacent to the contaminated groundwater plume, and whose microbial community exhibits either low or no contaminant metabolism is crucial for demonstrating adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolic adaptation by subsurface microorganisms to environmental pollutants at field sites can be documented using two principal types of criteria: the response may be qualitative, i.e., metabolism may be present in contaminated samples and absent in adjacent uncontaminated samples [6,20,32,35], or the response may be quantitative, i.e., prior exposure of microorganisms to a pollutant may shorten the lag period prior to the onset of metabolic activity [1,2], increase the rate or extent of metabolism, or enhance the proportion of the pollutant that is respired [2]. The presence of a control site that is uncontaminated, adjacent to the contaminated groundwater plume, and whose microbial community exhibits either low or no contaminant metabolism is crucial for demonstrating adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…and Traverse City, Michigan [2]. Although these settings represent a wide diversity of climatological, geologic, hydrologic, and other conditions, they all contained subsurface microbial communities that rapidly metabolized contaminant compounds inside but not outside the plume of contaminated groundwater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low biodegradability of xenobiotics may be due to the incapacity of microorganisms to effectively metabolize the organic compounds with uncommon chemical structures or properties; however, the microbial ability for the biodegradation of xenobiotics can be improved biologically by enrichment culture or adaptation to the specific organic compounds [3]. The time required for a bacterial community to mineralize xenobiotics and the concentration of xenobiotics may be a critical factor for determining degradation efficiency in wastewater treatment reactor [4,5]. Especially, the difference of persistence and initial concentration among xenobiotics contained in wastewater may be an important determinant for maintenance of bacterial community and biodegradability of individual xenobiotic [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, microbial degradation is a major loss pathway for PAHs from soil [1,2]. The ability of microbes to adapt to PAHs and the time required for adaptation to occur, in part, determines the persistence of organic contaminants [3]. For example, Johnson and Karlson [4] showed that previous exposure to PAHs at levels greater than background levels influenced adaptation and the ability of the indigenous microbes to degrade PAHs.…”
Section: Introductionmentioning
confidence: 99%